2014
DOI: 10.1186/1756-3305-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Climate and environmental change drives Ixodes ricinus geographical expansion at the northern range margin

Abstract: BackgroundGlobal environmental change is causing spatial and temporal shifts in the distribution of species and the associated diseases of humans, domesticated animals and wildlife. In the on-going debate on the influence of climate change on vectors and vector-borne diseases, there is a lack of a comprehensive interdisciplinary multi-factorial approach utilizing high quality spatial and temporal data.MethodsWe explored biotic and abiotic factors associated with the latitudinal and altitudinal shifts in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 81 publications
6
112
0
3
Order By: Relevance
“…The ability of two other variables (annual mean temperature and deer density) to act as a proxy of disease risk was also analysed, but their explanatory capability may only be satisfactory within certain intervals: the DIN was predicted to be negatively associated with annual temperature between 68C and 108C and positively with deer density between 15 and 22 head km 22 . Climate warming has been found to accelerate tick phenology [49] and contribute to their geographical expansion [54]. Our model predicted similar overall conclusions from applying scenarios of regional warming to the Lyme disease model.…”
Section: Discussionsupporting
confidence: 73%
“…The ability of two other variables (annual mean temperature and deer density) to act as a proxy of disease risk was also analysed, but their explanatory capability may only be satisfactory within certain intervals: the DIN was predicted to be negatively associated with annual temperature between 68C and 108C and positively with deer density between 15 and 22 head km 22 . Climate warming has been found to accelerate tick phenology [49] and contribute to their geographical expansion [54]. Our model predicted similar overall conclusions from applying scenarios of regional warming to the Lyme disease model.…”
Section: Discussionsupporting
confidence: 73%
“…3,16,17 This increase is secondary to a variety of influences including climate change resulting in the expansion of the Ixodes tick territory including expansion to higher elevations, changes in small mammal and deer populations, changes in deforestation and development, and improved reporting and awareness of disease. 3,8,[18][19][20][21] Some studies have suggested increased B burgdorferi virulence may be contributing to global spread; however, studies looking at B burgdorferi populations in the United States have been unable to validate this. 21,22 …”
Section: Geographic Distribution Of the Diseasementioning
confidence: 96%
“…The distribution of ticks and its associated diseases is increasing in many areas [2,3], and understanding the mechanisms provide potential for mitigation measures. Some of these increases can be linked to warmer climate, at least at higher elevation and latitudes [4].…”
Section: Introductionmentioning
confidence: 99%